Biology learning resources-based research of morphology insects in Lake Tondano - Masye Wurarah; Yermia Semuel Mokosuli; Sinyo Herry Sumampouw (JURNAL BIOEDUKATIKA, 2021)
Water hyacinth is a habitat for various types of insects in Lake Tondano. Insects that live in association with water hyacinth can be developed as a medium for learning biology. The biological characteristics of insects from Lake Tondano were developed into learning media to stimulate students' interest in learning. Students in this study are very familiar with Lake Tondano because it is a place for playing and recreation. This study aims to characterize the morphology, anatomy, and ecology of insects that live in association with water hyacinth in Lake Tondano. The method applied in this research is the research and development method of the 4D model. This research was carried out in two stages: the analysis of insects' biological characteristics in Lake Tondano and the development of biological learning media resources on Kingdom Animalia High School material. The results showed that the audiovisual learning media based on the analysis of media experts was in the high category (85.85%), material expert analysis was included in the high category (88.88%). Furthermore, the assessment by the biology teacher was high (88.67%). The test results in a small group of students, the feasibility response was high (86.2%). Based on the results of this study, this learning media is feasible to be applied in biology learning in high school for Kingdom Animalia material. The use of local biodiversity for education is influential in motivating students' interest in learning.